2018
DOI: 10.15244/pjoes/81294
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Raw Materials, Grinding Ratios, and Moisture Content During the Composting Process

Abstract: Composting as an environmental friendly treatment for efficiently decreasing solid waste volume and recycling organic nutrients is being incorporated into agricultural activities [1-3]. A successful composting process usually involves 4 phases: initial or rapid stage of temperature rise; semi-cure or biostabilization, when compost reaches the temperature above 55ºC [4]; the cure phase, with the start of humification and mineralization of organic matters [5]; and the last period of stability or maturation. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…A previous study showed that labile straw (lower C/N) has a stronger impact on soil aggregate stability than recalcitrant straw (higher C/N) (Zhao et al, 2018). Our meta-analysis consistently supported this finding, showing that the C/N ratios of straw from the three major grain crops of corn, rice, and wheat were in the following order: corn < rice < wheat (Wang et al, 2018), while the positive influences of straw return on soil macro-aggregates and stability were in the following order: corn > rice > wheat. Moreover, in the pot experiment, we found that the degree of soil aggregation in the soybean straw treatment with a low C/N ratio (48.21) was greater than that in the corn straw treatment with a high C/N ratio (78.55).…”
Section: Effects Of Straw Type On Soil Aggregatessupporting
confidence: 86%
“…A previous study showed that labile straw (lower C/N) has a stronger impact on soil aggregate stability than recalcitrant straw (higher C/N) (Zhao et al, 2018). Our meta-analysis consistently supported this finding, showing that the C/N ratios of straw from the three major grain crops of corn, rice, and wheat were in the following order: corn < rice < wheat (Wang et al, 2018), while the positive influences of straw return on soil macro-aggregates and stability were in the following order: corn > rice > wheat. Moreover, in the pot experiment, we found that the degree of soil aggregation in the soybean straw treatment with a low C/N ratio (48.21) was greater than that in the corn straw treatment with a high C/N ratio (78.55).…”
Section: Effects Of Straw Type On Soil Aggregatessupporting
confidence: 86%
“…5 a). Also, these bacteria at phylum level were observed in other waste composting (Wang et al 2017 ). The relative abundances of Proteobacteria, Bacteroidetes and Actinobacteria showed an increasing trend with the progress of the composting.…”
Section: Resultsmentioning
confidence: 70%